Self-fertility of Four Female Parent Clones of Ananas comosus L., involved in a 6x6 Complete Diallel Mating System with Selfings using the Typological Approach - Issali Auguste Emmanuel; Nguessan Angelo Evariste Badou; Mpika Joseph; Adiko Amoncho; Sangare Abdourahamane; Saraka Didier Martial; Deffan Zranseu Ange Bénédicte (Institute of Advanced Engineering and Science, 2013)
To determine the cropping type to apply to four clones of Ananas comosus in farms, their behaviour under hand selfings was analysed. 103-104-6, 410-106-33 and 410-200-15 hybrid female clones and RE43 Queen Victoria clone as well as HA10 and HA25 as controls were involved in a 6 x 6 complete diallel crossing system with selfings. The total seeds number derived from self hand-pollinations per week, mean seeds number obtained per self-pollinated flower and per week, weight of ripe fruit and bloomed flowers number per week were measured. The Anova, Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) were successively run. Results showed that 410-200-15 was revealed self-incompatible, while RE43 is found to be self-sterile. In the same way, 410-106-33 expresses self-sterile behaviour, whereas 103-104-6 shows the self-fertile one. The behaviour under selfings of both 410-200-15 and 410-106-33 comes from their HA10 Smooth Cayenne female parent which was previously characterised like self-incompatible. The structurings provided by the Anova and HCA are globally comparable. The 410-200-15 hybrid clone can already be recommended for on-farm trials under mono-crop. Nonetheless, the multi-crop will be envisioned once panmixia results will have demonstrated its inter-sterility. The 410-106-33 and 103-104-6 must be first subjected to successive back crosses before their on-farm trials. The RE43 clone must be cultivated in one crop. The morphological relatedness of five clones is discussed.